Knockdown resistance mutations are common and widely distributed in Xenopsylla cheopis fleas that transmit plague in Madagascar. - Shelby M Hutton; Adelaide Miarinjara; Nathan E Stone; Fara N Raharimalala; Annick O Raveloson; Ravo Rakotobe Harimanana; Mireille Harimalala; Soanandrasana Rahelinirina; Ryelan F McDonough; Abbe D Ames; Crystal Hepp; Minoarisoa Rajerison; et al. (Public Library of Science (PLoS), 2023)
Background Plague, caused by the bacterium Yersinia pestis, remains an important disease in Madagascar, where the oriental rat flea, Xenopsylla cheopis, is a primary vector. To control fleas, synthetic pyrethroids (SPs) have been used for >20 years, resulting in resistance in many X. cheopis populations. The most common mechanisms of SP resistance are target site mutations in the voltage-gated sodium channel (VGSC) gene. Methodology/principal findings We obtained 25 collections of X. cheopis from 22 locations across Madagascar and performed phenotypic tests to determine resistance to deltamethrin, permethrin, and/or dichlorodiphenyltrichloroethane (DDT). Most populations were resistant to all these insecticides. We sequenced a 535 bp segment of the VGSC gene and identified two different mutations encoding distinct substitutions at amino acid position 1014, which is associated with knockdown resistance (kdr) to SPs in insects. Kdr mutation L1014F occurred in all 25 collections; a rarer mutation, L1014H, was found in 12 collections. There was a significant positive relationship between the frequency of kdr alleles and the proportion of individuals surviving exposure to deltamethrin. Phylogenetic comparisons of 12 VGSC alleles in Madagascar suggested resistant alleles arose from susceptible lineages at least three times. Because genotype can reasonably predict resistance phenotype, we developed a TaqMan PCR assay for the rapid detection of kdr resistance alleles. Conclusions/significance Our study provides new insights into VGSC mutations in Malagasy populations of X. cheopis and is the first to report a positive correlation between VGSC genotypes and SP resistance phenotypes in fleas. Widespread occurrence of these two SP resistance mutations in X. cheopis populations in Madagascar reduces the viability of these insecticides for flea control. However, the TaqMan assay described here facilitates rapid detection of kdr mutations to inform when use of these insecticides is still warranted to reduce transmission of plague.